An Inexpensive, Easy‐to‐Use, and Highly Customizable Growth Chamber Optimized for Growing Large Plants. Issue 4 (13th February 2018) - Tran, Thu M.; Braun, David M.
Abstract: The ability to grow plants in highly controlled and reproducible environments is a critical factor for successful plant biology experiments. This protocol describes a simple and inexpensive method for constructing a fully automatic controlled growth chamber that can be easily adapted in plant biology laboratories as well as classrooms. All the materials described in this protocol can be found in garden and home improvement stores or through websites, making the procurement and setup for growing plants in a controlled environment less expensive and convenient. Furthermore, the system is highly customizable and can be used to study plant responses to numerous abiotic and biotic stress conditions. The growth chamber is designed to enable growth and characterization of large plants, such as maize and soybean. © 2017 by John Wiley & Sons, Inc.